If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2(x + -5) = 21x + -9 Reorder the terms: 4x + -2(-5 + x) = 21x + -9 4x + (-5 * -2 + x * -2) = 21x + -9 4x + (10 + -2x) = 21x + -9 Reorder the terms: 10 + 4x + -2x = 21x + -9 Combine like terms: 4x + -2x = 2x 10 + 2x = 21x + -9 Reorder the terms: 10 + 2x = -9 + 21x Solving 10 + 2x = -9 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 10 + 2x + -21x = -9 + 21x + -21x Combine like terms: 2x + -21x = -19x 10 + -19x = -9 + 21x + -21x Combine like terms: 21x + -21x = 0 10 + -19x = -9 + 0 10 + -19x = -9 Add '-10' to each side of the equation. 10 + -10 + -19x = -9 + -10 Combine like terms: 10 + -10 = 0 0 + -19x = -9 + -10 -19x = -9 + -10 Combine like terms: -9 + -10 = -19 -19x = -19 Divide each side by '-19'. x = 1 Simplifying x = 1
| 9-y=2y | | 17x+36=155 | | 2x^2+6x-94=0 | | 0=-16x^2+46x | | 3x+12y=15xy | | d+-951=-554 | | 91x^2+105x=-90 | | m*6*8:22=5/77*8 | | x^3-3x^2-4+12=0 | | 2x+8+4x+21+x-10=180 | | q-834=-65 | | (x+2)(x-3)-x(2x+1)+6x=0 | | 10(.5x+2)-5=3(x-6)+1 | | 14+3(6x-9)+12x=101 | | 6(7-2)= | | m*6=12 | | -6.5(2t+4)-1.2(4t-6)= | | 5f/10=f+2/6 | | g(x)=-2x^2-12x-14 | | g+-91=-75 | | 2x^2+18=54 | | 374=95x+75x | | n-8= 5 | | 2(5x-5)-6(x+8)=21 | | p+12p=-5 | | 2(3p+1)=8(4+p) | | 3=12-3r | | 31=z-12 | | 31=z-12 | | 204=90x+80x | | 3.954+26.7= | | 10y+29-8y=5y+5 |